PENINGKATAN KOMPETENSI GURU MELALUI PRODUKSI MEDIA POWERPOINT INTERAKTIF BERBASIS CANVA DI DESA WADUNG KECAMATAN PAKISAJI - Desinta Dwi Rapita; Sukma Ulandari; Devi Lestari; Munaisra Tri Tirtaningsih; Surya Desismansyah Eka Putra; Khofifatu Rohmah Adi; Kusnul Mubaroh (Dinamika Sosial: Jurnal Pendidikan Ilmu Pengetahuan Sosial, 2025)
This community service is motivated by the minimal use of technology in the learning process at educational institutions in Wadung Village. Therefore, training on the use of interactive media Canva is a strategic step in optimizing the use of infrastructure and improving teacher competency in Wadung Village. This community service uses a service learning method with the community as the main target. The community in this case is the teachers in Wadung Village, Pakisaji District, Malang Regency. The implementation of the community service begins with conducting coordination and initial observation, conducting training, implementation and mentoring as well as evaluation. The results of this activity are an increase in teacher competency in Wadung Village in creating interactive powerpoint media based on Canva, the creation of interactive powerpoint media based on Canva as an alternative learning media and the implementation of interactive powerpoint media based on Canva and Heyzine as a learning media in schools. ABSTRAK Pengabdian ini dilatarbelakangi oleh minimnya pemanfaatan teknologi dalam proses pembelajaran di lembaga pendidikan Desa Wadung. Oleh sebab itu pelatihan pemanfaatan media interaktif Canva merupakan langkah strategis dalam mengoptimalkan pemanfaatan sarana prasarana serta meningkatkan kompetensi guru di Desa Wadung. Pengabdian ini menggunakan metode service learning dengan masyarakat sebagai sasaran utama. Masyarakat dalam hal ini adalah guru-guru di Desa Wadung Kecamatan Pakisaji Kabupaten Malang. Pelaksanaan pengabdian dimulai dari melakukan koordinasi dan observasi awal, melaksanakan pelatihan, pengimplementasian dan pendampingan serta evaluasi. Hasil dari kegiatan ini adalah terjadi peningkatan kompetensi guru di Desa Wadung dalam membuat media powerpoint interaktif berbasis Canva, terciptanya media powerpoint interaktif berbasis Canva sebagai salah satu media pembelajaran alternatif serta pengimplementasian media powerpoint interaktif berbasis Canva sebagai media pembelajaran di sekolah.